Pelecehan Seksual Dalam Kacamata Sosial Media - Muhammad Irhamna Putra (IAIN Padangsidimpuan, 2021)
Sexual harassment is a social problem that is quite concerning and a serious problem that must be monitored. Sexual harassment is not free from acts of sexual violence, where the victims of this problem are both adults and children. This problem is a serious concern for the author, because there is still a lack of preaching and in-depth study of this issue. There is only one da'wah figure who discusses sexual harassment, Buya Yahya, through YouTube, explaining the issue. Using a qualitative approach with the message analysis method, this study found that the lack of information and information about sexual harassment was a separate task for preachers to overcome this problem in the future.